Altruism in the Perspective of the al-Qur'an and its Relevance to Philanthrophic Practices in Satu Amal Indonesia Organization - Azkiya, Nadia; Halimatussa'diyah, Halimatussa'diyah; Ilyas, Deddy (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This study investigates the altruism found in the al-Qur'an and its relevance to philanthropic practices in the Satu Amal Indonesia (SAI) organization. This study uses the maudhu'i interpretation method of the al-Qur'an verses related to altruism. In addition to the relevant verses of the al-Qur'an, this study collected data from respondents who filled out several questions through the Google Form. The data is then analyzed in the context of altruistic values and their relevance to philanthropic practices in SAI. This study reinforces previous research that the millennial generation tends to have philanthropic behavior. The millennial generation of members of the SAI organization internalizes and applies the values of altruism contained in the al-Qur'an. In addition, this study reveals that SAI members tend to participate in philanthropic activities carried out online and use social media as a platform for promotion. Overall, this study shows that the millennial generation, particularly members of SAI, apply the value of altruism and show philanthropic behavior; the same values are taught in the Qur'an, to be precise in Q.s. al-Hasyr verse 9. The values of altruism are reflected in patterns of caring, collaborating, sustainable, and cooperative attitudes.